1264. In Vitro Activity of Ceftazidime-Avibactam and Comparator Agents Against Enterobacterales and Pseudomonas aeruginosa Collected < 48 Hours and ≥48 Hours Post-Admission from Pediatric Patients, ATLAS Surveillance Program 2016-2019. (4th December 2021) - Kazmierczak, Krystyna; Lob, Sibylle; Stone, Gregory; Sahm, Daniel F
Abstract: Background: Ceftazidime-avibactam (CAZ-AVI) is a β-lactam/non-β-lactam β-lactamase inhibitor combination with in vitro activity against Enterobacterales (Ent) and Pseudomonas aeruginosa ( Psa ) carrying Class A, C and some Class D β-lactamases. We examined the in vitro activity of CAZ-AVI and comparators against presumed community-acquired (CA; cultured < 48 h after hospital admission) and hospital-acquired (HA; cultured ≥48 h post-admission) isolates collected from pediatric patients as part of the ATLAS surveillance program. Methods: 6654 non-duplicate isolates were collected in 52 countries in Europe (n=3423), Latin America (n=1323), Middle East/Africa (n=1177), and Asia/Pacific (excluding China; n=731) from patients (newborn to 17 y) with lower respiratory tract (LRTI; n=1687), urinary tract (UTI; n=1631), bloodstream (BSI; n=1149), skin and soft tissue (SSTI; n=1122), and intra-abdominal (IAI; n=981) infections. Susceptibility testing was performed by CLSI broth microdilution and values were interpreted using CLSI 2021 breakpoints. CAZ-AVI was tested at a fixed concentration of 4 µg/mL AVI. Isolates with CAZ or aztreonam MICs ≥2 µg/mL ( Escherichia coli, Klebsiella spp., Proteus mirabilis ) or meropenem MICs ≥2 µg/mL (all Ent species) or ≥4 µg/mL ( Psa ) were screened for β-lactamase genes. Results: The in vitro activity of CAZ-AVI exceeded that of meropenem and other tested β-lactams against Ent (97.8% susceptible (S)) and Psa (92.1% S) collected globally from pediatric patients (Table). Percentages of susceptibility to CAZ-AVI ranged from 95.4-99.2% among CA Ent from different infection types and were reduced 0.6-1.3% among HA isolates from LRTI, UTI, SSTI, and IAI. Susceptibility to CAZ-AVI was also similar (92.6-95.8% S) among CA Psa from different infection types and was reduced 1.2-7.0% among HA isolates. Larger differences in susceptibility were typically seen for the tested comparator β-lactams. For Ent, the lowest percentages of susceptibility to the tested β-lactams were observed among isolates from BSI, while the pattern was less clear for Psa . Results Table Conclusion: CAZ-AVI could provide a valuable therapeutic option for treatment of CA and HA infections caused by Ent and Psa in pediatric patients. Disclosures: Krystyna Kazmierczak, PhD, IHMA (Employee)Pfizer, Inc. (Independent Contractor) Sibylle Lob, PhD, IHMA (Employee)Pfizer, Inc. (Independent Contractor) Gregory Stone, PhD, AztraZeneca (Shareholder, Former Employee)Pfizer, Inc. (Employee) Daniel F. Sahm, PhD, IHMA (Employee)Pfizer, Inc. (Independent Contractor)